2008
DOI: 10.1016/j.canlet.2007.10.019
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant expression of selenoproteins in the progression of colorectal cancer

Abstract: Since damage to DNA and other cellular molecules by reactive oxygen species ranks high as a major culprit in the onset and development of colorectal cancer, the aim of the present study is to clarify the role of antioxidant seleonoproteins including glutathione peroxidase (GPx), thioredoxin reductase (TXR) and selenoprotein P (SePP), and the effect of oxidative stress on the progression of colorectal cancer. Expression of 14 oxidative stress-related molecules in both tumorous and non-tumorous tissues in 41 pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
82
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(90 citation statements)
references
References 34 publications
6
82
0
Order By: Relevance
“…283 GPx2 is upregulated in some types of cancer, particularly of gastrointestinal origin. 284 A recent study has shown that lower expression of GPx2 increases migration and invasion of cancer cell clones, but decreases their growth, thus depending on the stage of tumour development. 285 Finally, TrxR1 is probably the most investigated Se-protein in its relationship to cancer.…”
Section: Male Infertilitymentioning
confidence: 99%
“…283 GPx2 is upregulated in some types of cancer, particularly of gastrointestinal origin. 284 A recent study has shown that lower expression of GPx2 increases migration and invasion of cancer cell clones, but decreases their growth, thus depending on the stage of tumour development. 285 Finally, TrxR1 is probably the most investigated Se-protein in its relationship to cancer.…”
Section: Male Infertilitymentioning
confidence: 99%
“…High Se supplementation (2 lg/g body weight) was shown to prevent inflammation and improve the health of affected tissue in a rat model of dextran sodium sulfate (DSS)-induced colitis (249). Selp is among the selenoproteins expressed at the highest levels in the intestine (104,179), and this protein may play a particularly important role in the pathogenesis of colitis. In a mouse model of colitis utilizing DSS treatment, Selp mRNA was decreased in the colon of DSS-treated mice (237).…”
Section: Intestinal Inflammation and Food-borne Illnessesmentioning
confidence: 99%
“…4). The different regulation of the glutathione peroxidase isoenzymes is intriguing with regard to the opposite distribution of GPx1 and GPx2 along the crypt to villus axis in the intestine and their reciprocal expression pattern in tumorous versus nontumorous human colon tissue, as reported by others (10,12,44).…”
Section: Differentiation Triggers An Increase In Gpx4 Protein Expressmentioning
confidence: 75%